575. MANUAL LAYER EMBEDDED ANASTOMOSIS: A NEW TECHNIQUE TO REDUCE ANASTOMOSIS LEAKAGE AFTER ESOPHAGECTOMY. (24th September 2022) - He, Xuedong; Han, Yongtao; Peng, Lin; Mao, Tianqin; He, Wenwu
Abstract: The suturing after esophagectomy includes mechanical anastomosis and hand-sewn anastomosis. At present, various of anastomosis methods with potential anastomosis leakage, the optimal anastomosis methods still remain debates. This study described a new technique for creation of an anastomosis in thought to reduce the incidence of anastomosis leakage. Between September 2020 to December 2021, the patients who received this new anastomosis technique enrolled into this retrospective study. The anastomosis method as follows. Firstly, the gastric conduit was shaped secondary to get adapt embedded length and anger. Secondary, the embedded posterior wall was sutured and layer sew anastomosis. And then, embedded the anastomosis after layer sew into gastric tube and suture the embedded anterior wall lastly. And the anastomosis was pushed into thorax from neck to ended this anastomosis procedure. A total of 56 patients enrolled into this study comprised 51 males and 5 females with mean age of 65.4 years. Among of them 9 patients received neoadjuvant therapy. And all of them performed minimally invasive surgery by thoracoscope combined laparoscopic. The median intraoperative blood loss volume was 79.8ml (range 20-150ml). The median operate time was 331 minutes (range 220-465 minutes). The median postoperative feeding time was 6.3 days (range 3-8 days). All the patients without anastomosis leakage. The incidence of anastomotic stricture and the acid reflux ration were lower than the average of literature reports. This new manual layered embedded esophagogastric anastomosis significantly reduce the incidence of anastomosis leakage and stricture, prevent the acid reflux. This technique has good short outcome and suitable for popularization and application.